SUKAN WARNA: MENGHIDUPKAN SPORTIFITAS DAN BUDAYA ISLAM MELAYU DI SEKOLAH SRITENGO WITTAYA, THAILAND: SPORTS COLOR: REVIVING SPORTSMANSHIP AND MALAY ISLAMIC CULTURE AT SRITENGO WITTAYA SCHOOL, THAILAND - Muhammad Azam Azzumar; Abdul Rohim (Pakis Journal Institute, 2023)
The Celebration of Sukan Warna (Colorful Sports) at Sritengo Wittaya School is a successful effort in preserving culture, promoting the school, and strengthening relationships among students, teachers, and the local community. The event spans two days, with the first day marked by a vibrant parade of traditional Malay costumes. On the second day, various spirited physical competitions take place, complemented by several creative contests originating from Indonesia. The outcome is a triumphant celebration that fulfills its goals and serves as an inspiration for broader community engagement, fostering positive relations within the Muslim community in Thailand. This community engagement aims to investigate the role and significance of Sukan Warna as a means of reinforcing cultural identity at Sritengo Wittaya School in Narathiwat Province, Thailand. In this school environment, Sukan Warna serves not only as a competitive arena but also as a platform to celebrate and preserve the cultural heritage and traditions of the Muslim community in the region. The research methodology involves participatory observation, interviews with relevant stakeholders, and documentation of the Sukan Warna event held at the school. Through this approach, data regarding the series of activities, participant roles, and the impact of Sukan Warna on strengthening cultural identity are collected and analyzed. The findings of this community engagement reveal that Sukan Warna at Sritengo Wittaya School serves as a significant avenue for students to express, celebrate, and uphold the cultural heritage and traditions of the Muslim community in Narathiwat Province. This event not only strengthens social bonds among students but also nurtures a sense of pride in their cultural identity.